Ethical values in archival arrangement and description: An analysis of professional codes of ethics - Da Silva, Andrieli Pachú [UNESP]; Guimarães, José Augusto Chaves [UNESP]; Tognoli, Natália Bolfarini [UNESP] (My University, 2015)
The international literature on information science has devoted attention to ethical studies in information, especially due to the development of information technologies. However, the information organization activities have incipient ethical studies that are mostly focused on libraries. Thus, the area of archival science still lacks studies of this nature, which leads to question how the codes of ethics for archivists address issues related to ethical dilemmas of information organization activities, especially in core activities of arrangement and document description. Thus, this study aims to identify and analyze ethical values related to those aforementioned activities, by analyzing the codes of the following countries: Brazil, Portugal, France, Spain, Australia, Canada, USA, New Zealand, United Kingdom and Switzerland and the ICA codes of ethics. Applying a content analysis, the following values were found: access and use, authenticity, confidentiality, conservation, custody, impartiality, information access, information security, physical preservation of the record, reliability, respect for provenance, respect for the original order, respect for the preservation of the archival value of the record.
Keywords: Archival arrangement; Archival classification; Archival description; Ethical values; Information; Respect